Sustainable Green Synthesis of Yttrium Oxide (Y2O3) Nanoparticles Using Lantana camara Leaf Extracts: Physicochemical Characterization, Photocatalytic Degradation, Antibacterial, and Anticancer Potency - Rajakumar Govindasamy; Mydhili Govindarasu; Salman S. Alharthi; Preeyanghaa Mani; Neppolian Bernaurdshaw; Thandapani Gomathi; Mohammad Azam Ansari; Mohammad N. Alomary; Banan Atwah; M. Shaheer Malik; V. Devi Rajeswari; Kaliaperumal Rekha; et al. (Nanomaterials, 2022)
Due to their appropriate physicochemical properties, nanoparticles are used in nanomedicine to develop drug delivery systems for anticancer therapy. In biomedical applications, metal oxide nanoparticles are used as powerful and flexible multipurpose agents. This work described a green synthesis of Y2O3 nanoparticles (NPs) using the sol-gel technique with the use of aqueous leaf extracts of Lantana camara L (LC). These nanoparticles were characterized with the aid of different methods, including UV, X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FTIR), transmitted electron microscopy (TEM), and photocatalytic degradation. Y2O3 nanoparticles showed excellent antibacterial activity against Gram-positive Bacillus subtilis and Gram-negative Escherichia coli with a 10 to 15 mm inhibitory zone. Green Y2O3 NPs were released with a 4 h lag time and 80% sustained release rate, indicating that they could be used in drug delivery. In addition, the bioavailability of green Y2O3 NPs was investigated using cell viability in cervical cancer cell lines. These green-synthesized Y2O3 NPs demonstrated photocatalytic degradation, antibacterial, and anticancer properties.